2022
DOI: 10.3390/jof8040382
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Two Major Implantation Mycoses: Chromoblastomycosis and Sporotrichosis

Abstract: Chromoblastomycosis and sporotrichosis are the two main implantation mycoses that are now recognized as fungal neglected tropical diseases (NTDs). Their laboratory diagnosis mainly relies on direct microscopy, histopathology, and identification of the fungus by culture. However, to be appropriately used, these techniques require mycological expertise that is not widely available and may be absent in peripheral health care facilities in endemic areas. In addition, they lack sensitivity and specificity, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Sporotrichosis is a fungal infection primarily found in tropical and subtropical regions, including countries such as Brazil, India, Mexico, the USA, Japan, China, Madagascar and South Africa 12 . Our study revealed that not all countries have reported cases of sporotrichosis in people living with HIV (PLWH), which suggests possible underreporting and underdiagnosis of such cases.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Sporotrichosis is a fungal infection primarily found in tropical and subtropical regions, including countries such as Brazil, India, Mexico, the USA, Japan, China, Madagascar and South Africa 12 . Our study revealed that not all countries have reported cases of sporotrichosis in people living with HIV (PLWH), which suggests possible underreporting and underdiagnosis of such cases.…”
Section: Discussionmentioning
confidence: 78%
“…Sporotrichosis is a fungal infection primarily found in tropical and subtropical regions, including countries such as Brazil, India, Mexico, the USA, Japan, China, Madagascar and South Africa. 12 Our study revealed that not all countries have reported cases of sporotrichosis in people living with HIV (PLWH), which suggests possible un- identifications, as well as an in vitro thermoconversion test. 17 In addition, special histological staining techniques can be used, such as Periodic Acid Schiff and Gomori-Grocott silver methenamine, in cases where there is suspicion of sporotrichosis associated with a histopathological picture compatible with the disease.…”
Section: Discussionmentioning
confidence: 80%
“…Currently, there is no existing literature on assays for the identification of CBM and FEO agents using RFLP, with only isolated studies of specific primers which either do not encompass all currently identified agents or lack sensitivity and specificity [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the absence of histopathology laboratories in remote areas probably limits the availability of early diagnosis. New diagnostic tests are based on the detection of specific biomarkers or DNA sequencing, but this raises the question of their accessibility in endemic countries with limited resources [ 25 , 26 , 27 ]. The proportion of diagnoses by direct examination was low, given the easiness of this procedure.…”
Section: Discussionmentioning
confidence: 99%